2017
DOI: 10.1159/000456046
|View full text |Cite
|
Sign up to set email alerts
|

Up-Regulation of TGF-β Promotes Tendon-to-Bone Healing after Anterior Cruciate Ligament Reconstruction using Bone Marrow-Derived Mesenchymal Stem Cells through the TGF-β/MAPK Signaling Pathway in a New Zealand White Rabbit Model

Abstract: Background/Aims: This study aimed to explore the role of TGF-β in tendon-to-bone healing after anterior cruciate ligament (ACL) reconstruction using bone marrow-derived mesenchymal stem cells (BMSCs) through the TGF-β/MAPK signaling pathway in a New Zealand white rabbit model. Methods: A total of 72 healthy male New Zealand white rabbits were selected for these experiments. Flow cytometry and immunofluorescence were used to detect the expression of BMSC surface markers, and qRT-PCR was performed to detect TGF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
45
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 36 publications
2
45
0
1
Order By: Relevance
“…TGF-β is an important growth factor known to participate in the formation of several tissues through production of extracellular proteins, regulation of matrix metalloproteinases, and proliferation of fibroblasts during the wound healing process, including in bone. 20,21,22 TGF-β may be involved in callus formation, osteoclast apoptosis, and inhibition of osteoclast activation. 20,23,24 Produced by platelets, chondrocytes and osteoblasts, TGF-β is released during bone turnover and regeneration, and can be deposited in the bone matrix, where it stimulates proliferation of mesenchymal stem cells, preosteoblasts, chondrocytes, and osteoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β is an important growth factor known to participate in the formation of several tissues through production of extracellular proteins, regulation of matrix metalloproteinases, and proliferation of fibroblasts during the wound healing process, including in bone. 20,21,22 TGF-β may be involved in callus formation, osteoclast apoptosis, and inhibition of osteoclast activation. 20,23,24 Produced by platelets, chondrocytes and osteoblasts, TGF-β is released during bone turnover and regeneration, and can be deposited in the bone matrix, where it stimulates proliferation of mesenchymal stem cells, preosteoblasts, chondrocytes, and osteoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Kovacevic et al ( 22 ) combined TGFβ3 with an injectable Ca-P matrix and demonstrated that it may improve healing following rotator cuff repair. A recent study demonstrated that upregulating TGFβ expression in bone mesenchymal stem cells (BMSCs) can promote tendon-to-bone healing following ACL reconstruction by regulating the TGFβ1 mitogen-activated protein kinase (MAPK) 1 signaling pathway ( 23 ). In addition, TGFβ1 is the most important fibrosis inducer ( 24 ), which could explain the increase in collagen fibers.…”
Section: Discussionmentioning
confidence: 99%
“…Many growth factors have been discovered and applied to tissue engineering technology, including transforming growth factor-β (TGF-β) [27], epidermal growth factor (EGF) [28], vascular endothelial growth factor (VEGF) [29], and fibroblast growth factor (FGF) [30]. Among them, FGF-2 (basic fibroblast growth factor) has been widely used in tissue engineering technology due to its unique advantages [31].…”
Section: Introductionmentioning
confidence: 99%